Fabrication of polyethersulfone electrospun nanofibrous membranes incorporated with hydrous manganese dioxide for enhanced ultrafiltration of oily solution - Al-Husaini, I.S. (2019)
In this work, a new type of ultrafiltration (UF) electrospun nanofibrous membranes (ENMs) incorporating hydrous manganese dioxide (HMO) nanoparticles was fabricated with the objective of improving properties of polyethersulfone (PES)-based membrane for synthetic oily solution treatment. Two treatments were carried out to improve the mechanical property and hydrophilicity of the PES-based membrane without compromising its porosity and water permeance. The first treatment involved the use of mixed solvents â dimethylformamide and n-methyl-pyrrolidinone (DMF/NMP) in which NMP is a high vapor pressure component that could enhance the mechanical properties of the nanofibrous by improving solvent-induced fusion of inter-fiber junction points. The second treatment involved the incorporation of specific amount of HMO nanoparticles in PES dope solution to enhance membrane hydrophilicity. Heat treatment was also adopted as an effective approach to strengthen and prevent delamination of the nanofibrous mat during UF process. The HMO-incorporated ENMs exhibited an excellent oil rejection (97.98 and 94.04) and a promising water flux recovery (89.29 and 71.10) when used to treat a synthetic oily solution containing 5000 or 10,000 ppm oil, respectively. The best promising HMO-incorporated ENM exhibited much higher magnitude of water productivity (>7000 L/m2h) without sacrificing oil removal rate. Most importantly, this nanofillers-incorporated membrane showed significantly lower degree of flux decline as a result of improved surface resistance against oil fouling and is of potential for long-term operation with extended lifespan. The promising mechanical and anti-fouling properties of the ENMs is potentially applicable in the efficient industrial oily effluents treatment when challenged with oil-in-water emulsions. Â© 2018 Elsevier B.V.